Identification of Azo Dye Degrading Sphingomonas Strain EMBS022 and EMBS023 Using 16S rRNA Gene Sequencing - G. Nadh, Anuroopa; Raj Akare, Uday; Sharma, Priya; Yadav, Pratibha; Bandaru, Srinivas; Nayarisseri, Anuraj; S. Nair, Achuthsankar (Current Bioinformatics, 2015)
Azo dyes form substantial industrial pollutants owing to their poor biodegradation capacity. Present study identifies azo dye detoxifying strain of bacteria from waste water near textile industries. In order to identify the azo dye degrading strain, 16S rRNA gene was sequenced from the pure bacterial culture obtained from the samples collected from textile industry area at Erode in Tamil Nadu state of India. Two novel azo dye degrading bacteria were found out of 60 samples investigated, which were respectively named Sphingomonas sp strain EMBS022 and Sphingomonas sp strain EMBS023. Isolates of Sphingomonas sp strains - EMBS022 and EMBS023 were deposited in GenBank with accession numbers ‘KF951596’ & ‘KF951597’respectively. UNAFOLD and RNA fold web servers were employed to predict the secondary structure of 16s RNA of these strains. Free energy estimate for secondary structures of 16s rRNA of strains EMBS022 and EMBS023 were ΔG = -159.00 kcal/mol and ΔG = -159.90 kcal/mol, confirming the structures to be considerably stable.
Keywords: Sphingomonas sp strain EMBS022 and EMBS023